2018
DOI: 10.1101/385716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mini viral RNAs act as innate immune agonists during influenza virus infection

Abstract: and propose an intramolecular copy-choice mechanism for mvRNA generation. 43 By deep-sequencing RNA samples from lungs of ferrets infected with influenza 44viruses we show that mvRNAs are generated during infection of animal models. 45 We propose that mvRNAs act as main agonists of RIG-I during influenza virus 46infection and the ability of influenza virus strains to generate mvRNAs should be 47 considered when assessing their virulence potential. 48The negative sense viral RNA (vRNA) genome segments of influe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 51 publications
(37 reference statements)
2
42
1
Order By: Relevance
“…Besides these different responses, most of which are IFN-mediated, small non-coding (micro, circular, ...) RNAs, RNAi, and IFN-independent antiviral responses can be regarded as part of the innate immune response package as well [29][30][31]. An emerging hot topic is also the interplay of innate immune response with cellular metabolism, so-called immunometabolism, which likely is quite relevant for respiratory viral infections [4,32,33].…”
Section: Importance and Composition Of Innate Immune Responses Againsmentioning
confidence: 99%
“…Besides these different responses, most of which are IFN-mediated, small non-coding (micro, circular, ...) RNAs, RNAi, and IFN-independent antiviral responses can be regarded as part of the innate immune response package as well [29][30][31]. An emerging hot topic is also the interplay of innate immune response with cellular metabolism, so-called immunometabolism, which likely is quite relevant for respiratory viral infections [4,32,33].…”
Section: Importance and Composition Of Innate Immune Responses Againsmentioning
confidence: 99%
“…To this end, we found that infection with the untargeted NP control virus resulted in the accumulation of full length vRNA and the previously characterized small viral RNA (svRNA) ( Figure 3A) (Perez et al, 2010;Perez et al, 2012;Umbach et al, 2010). In contrast, while a complete loss of full length vRNA was observed in the NPtargeted virus, these same conditions showed the accumulation of a range of smaller viral RNA species comparable in size to the recently described mini viral RNA (mvRNA) -an NP-independent DVG ( Figure 3A) (Te Velthuis et al, 2018). In agreement with mvRNA being a potent inducer of the antiviral response, we also observed a correlation between its appearance and the induction of IFN ( Figure 3B).…”
Section: Np Influences Rdrp Processivity and Dvg Levels Of Negative-smentioning
confidence: 69%
“…As new genomes are generated, there is an immediate demand for available NP pools. As this dynamic progresses, NP inevitably becomes limiting thereby forming only a partial RNP complex, which promotes the formation of DVGs, perhaps in part by providing the viral RdRp with more flexibility to slide or disengage from the template strand during replication (Te Velthuis et al, 2018). DVGs generated by this process further exacerbate the problem as they too can be substrates for NP and the polymerase, thereby overwhelming the resources of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…But in a delicate balance, this immune response to an infection can also be harmful to the host. For example, an excessively pro‐inflammatory cytokine and chemokine environment has been cited as the key explanation for the severity of human infections with highly pathogenic avian influenza, and the 1918 H1N1 “Spanish flu” pandemic . This “cytokine storm” can rapidly result in multi‐organ dysfunction and acute respiratory distress syndrome (ARDS).…”
Section: Introductionmentioning
confidence: 99%
“…For example, an excessively pro-inflammatory cytokine and chemokine environment has been cited as the key explanation for the severity of human infections with highly pathogenic avian influenza, and the 1918 H1N1 "Spanish flu" pandemic. 10 This "cytokine storm" can rapidly result in multi-organ dysfunction and acute respiratory distress syndrome (ARDS). Similarly, in seasonal influenza damage to the airways and alveolae is mediated both by viral replication and by the innate immune response.…”
Section: Introductionmentioning
confidence: 99%